PROLONGED DURATION AND DOSE OF METFORMIN THERAPY AND ITS ASSOCIATED EFFECT OF VITAMIN B12 DEFICIENCY AMONG TYPE II DM PATIENTS: A CROSS SECTIONAL STUDY. - Andrew Gnanaprakasam J; Veeramani G; Manjanna K (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Objective: The aim of the study is to observe the long-term treatment of metformin and its associated effect on Vitamin B12 among Type II Diabetes mellitus south Indian patients. Methods: An observational study conducted over a period of 54 months on Type II Diabetes mellitus patients who are in chronic therapy with metformin. The study described the Vitamin B12 levels among the Type II DM patients, which could alert the patients who are in the low and borderline range of serum Vitamin B12, which may prevent the risk of peripheral neuropathic complications and anaemic conditions, etc. Findings: Totally, 387 patients were enrolled as per the inclusion and exclusion criteria, including 232 males (59.94%) and 155 females (40.05%). A total of 39 patients had been observed to have low levels of Vitamin B12, among them 23 females (Mean 184.17 ± S.D. 10.69) and 16 males (Mean 185.31± S.D 7.56), followed by 16 patients found to be above the normal range of Vitamin B12, among them 02 females (Mean 991 ± S.D. 15.55) and 14 males (Mean 1578.14 ± S.D. 406.93), followed by 76 patients had been found to be borderline of Vitamin B12, among them 43 females (Mean 220.76 ± S.D 6.50). Conclusion: High doses of chronic Metformin therapy may alter Vitamin B12 levels. Some of the patients had an abnormally high level of serum Vitamin B12, whose medical condition should be ruled out, and such Patients’ diet histories were also cross-examined, which was a mixed normal diet, and they had various medical conditions. However, the high chances of metformin-associated effects on Vitamin B12 with higher doses and long-term therapy of metformin, whose duration was 10 to 20 years, Moreover, age is also an important factor, and the study reveals that, among genders, female populations had a higher rate of low-level Vitamin B12 than male populations. Patients in the age group between 50 and 65 years had a higher rate of low-level Vitamin B12 than other age groups, totaling 20 patients, among them 12 females (Mean 183.08 ± S.D. 13.17) and 8 males (Mean 185.5 ± S.D. 4.3). Patients with other comorbid conditions also had low levels and borderline levels of Vitamin B12 and had been on long-term metformin therapy. Therefore, our study concluded that chronic therapy and higher doses of metformin may lead to a deficit in serum Vitamin B12, which requires regular checks on Vitamin B12 among Type 2 DM patients to avoid the risk of Peripheral neuropathy and other complications.